2015
DOI: 10.3109/10428194.2015.1075019
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 trial of carfilzomib (PR-171) in combination with vorinostat (SAHA) in patients with relapsed or refractory B-cell lymphomas

Abstract: A phase 1 study with carfilzomib and vorinostat was conducted in 20 B-cell lymphoma patients. Vorinostat was given orally twice daily on days 1, 2, 3, 8, 9, 10, 15, 16, and 17 followed by carfilzomib (given as a 30 min infusion) on days 1, 2, 8, 9, 15, and 16. A treatment cycle was 28 days. Dose escalation initially followed a standard 3+3 design, but adapted a more conservative accrual rule following dose de-escalation. The maximum tolerated dose was 20 mg/m2 carfilzomib and 100 mg vorinostat (twice daily). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…However, combined exposure induced more pronounced tumor growth suppression in a xenograft MCL model and a significant improvement in survival compared to single agents, arguing that this strategy may preferentially kill lymphoma versus normal cells. In this context, a recent phase I trial in patients with refractory NHL has demonstrated that a regimen combining CFZ with the pan-HDACI vorinostat is tolerable and displays some, albeit modest activity (49). If a more selective HDACI induces less toxicity, higher drug doses and greater regimen activity may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, combined exposure induced more pronounced tumor growth suppression in a xenograft MCL model and a significant improvement in survival compared to single agents, arguing that this strategy may preferentially kill lymphoma versus normal cells. In this context, a recent phase I trial in patients with refractory NHL has demonstrated that a regimen combining CFZ with the pan-HDACI vorinostat is tolerable and displays some, albeit modest activity (49). If a more selective HDACI induces less toxicity, higher drug doses and greater regimen activity may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data have shown synergy between HDACI and proteasomal inhibition via apoptosis in DLBCL [49]. This was tested in a phase I trial of carfilzomib in combination with vorinostat in R/R DLBCL [50]. The combination was well tolerated and 2/20 patients had stable disease.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of some of these novel agents with other novel or traditional agents have been explored (Table 3). Some recent clinical trials indicate that a newer proteasome inhibitor (Carfilzomib) can be combined with other agents including bendamustine, BEAM regimen followed with ASCT or CDK9 inhibitor although neurotoxicity may be a limiting factor [126129]. Lenalidomide, an immunomodulatory agent, has shown promising results in MCL cases refractory to bortezomib, and in cases previously treated with other agents or combinations [124,130].…”
Section: Treatment Of Relapse/refractory MCLmentioning
confidence: 99%